Revision of the West Seti Dam Design in Nepal (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Recent research on the effects of seismic activity on concrete faced rock-filled dams (CFRD) is examined in light of the potential CFRD-type West Seti Dam under consideration in Nepal. Revision of Nepal’s West Seti Dam design is recom-mended.Key words: Concrete faced rock-filled dams (CFRD); Seismic activity; West Seti Dam; NepalDOI: 10.3126/hn.v6i0.4195Hydro Nepal Journal of Water, Energy and Environment Vol. 6, January 2010Page: 52-54Uploaded Date: 24 January, 2011